Physical development of children of the city Dnipro, patients with cystic fibrosis. - N. N. Kramarenko; S. H. Ivanus (Medičnì Perspektivi)
36 children with cystic fibrosis are inspected. Certain modern problems of children’s cystic fibrosis and questions related with warning and slowing down unfavorable consequences of illness in the future are determined. Data of cystic fibrosis prevalence and morbidity in Dnepr for the last 5 years are analyzed. Epidemiology of disease, clinic-anamnesis data, laboratory instrumental indexes of our patients are analyzed. Anthropometric measuring of body mass, height, chest circumference, somatoscopic research, calculation of trophic index is conducted. Features of physical development and nutritional state of children with cystic fibrosis, which consist in the substantial decline of body weight in disharmonized development are found. Certain degrees of protein-power insufficiency are determined. The relationship of these features with the function of the external breathing, duration and severity of disease is analyzed.